Chicago Architecture and Design - Pridmore, Jay; Larson, George A; Photography by Bleesing, Hedrich (New York Harry N, 2005)
Chronicles Chicago architecture from the nineteenth through early twenty-first centuries, and examines the evolution of the skyscraper, sculptures and signature works, and more
Include Color Illustrations, Glossary, Bibliography and Index
Keywords: Illinois--Chicago -- Architecture -- Buildings